Taxonomic composition and systematic structure of dendroflora of the national natural park "Burabay" (Experimental biology, 2016)
The article presents the results of research carried out in the national park "Burabay" (2010-2015), gives the taxonomic analysis of the tree and shrub flora and provides with the information on the composition and systematic structure of park dendroflora. The flora of the State National Natural Park "Burabay" includes 94 species of woody plants. They belong to 30 families, 53 genera and 2 divisions. The dendroflora comes up to 14.6% of the total flora of the park. The dominant in amount and genera are the families: Rosaceae; Salicaceae; Grossulariaceae. The ratio of the number of species and genera in flora can be the indicator of allochthonous and autochthonous trends in flora development. The more the average number of species in a genus is, the more obvious the autochtonus processes in the formation of the flora have been expressed, the lower this index is, the greater role the migrations of species played in the process of florogenesis. A negative value of the independence index obtained in the study of flora in the SNNP "Burabay" shows the predominance of allochthonous trends in the development of dendroflora and a large role of species migration It was made the analysis of vitality of the tree-shrub flora.
Keywords: national park; dendroflora; systematic structure; taxonomic composition; arboriflora